DEVELOPMENT OF MATHEMATICS MODULE WITH NUMBERED-HEADS TOGETHER (NHT) COOPERATIVE LEARNING MODEL ON SQUARE AND TRIANGLE FOR JUNIOR HIGH SCHOOL - Hujjatul Muslimah; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
This research is based on the less optimal use of student books as teaching material and unavailability of modules, mainly facilitating students to learn in groups. Modules with NHT cooperative learning model can be used as teaching materials to ease students in learning mathematics by group discussion. This development research aims to manage and develop teaching materials in the form of Mathematics Module with Numbered-Heads Together (NHT) Cooperative Learning Model on the two-dimensional figure (Square and Triangle) for VII grade students. This study also aims to determine the feasibility of modules developed based on material experts, media experts, and student responses. This research was conducted using the ADDIE development model. The development steps include Analysis, Design, Development, Implementation, and Evaluation. The Mathematics Module on two-dimensional figures (Square and Triangle) for grade VII Students is developed by integrating NHT cooperative learning steps. This product has passed through a revision phase based on the advice and inputs of material experts and media experts. This research shows that the teaching materials in the form of Mathematics Module with Numbered-Heads-Together (NHT) Cooperative Learning Model on the two-dimensional figure (Square and Triangle) for Junior High School Students in Grade VII have excellent quality proven from validity criteria. Based on the materials expert assessment, the average score of 137 meets the very - good criteria, and the assessment of media experts obtained an average of 136.3 that fulfills the criteria very well. The students' responses obtained an average of 131.6, which meets the criteria very well as well. Based on the results of the research, the Mathematics Module with Numbered-Heads-Together (NHT) Cooperative Learning Model on two-dimensional figure material (Square and Triangle) for Junior High School Students in Grade VII is suitable for mathematics learning.